Loss on ignition of sediment core IZN_19-31 from Lake Iznik (NW Turkey) - Gastineau, Renaldo; De Sigoyer, Julia; Sabatier, Pierre; Fabbri, Stefano C; Anselmetti, Flavio S; Develle, Anne-Lise; Şahin, Mustafa; Gündüz, Serkan; Niessen, Frank; Gebhardt, Andrea Catalina (PANGAEA, 2020)
The loss on ignition (LOI) analysis was performed in 2019 on the IZN19_31 Sequence, with a 10-cm sampling interval all along the sequence to estimate organic matter (OM) and carbonate proportion in the sediment, following the protocol described by Heiri et al., (2001; doi:10.1023/A:1008119611481).
Keywords: Iznik; Lake; sediment analysis; Turkey